Semiotika Adat Gusaran di Kecamatan Cibingbin Kabupaten Kuningan - Tri Hardianti Lukman; Opah Ropiah (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2023)
Semiotics in Cibingbin District, Kuningan Regency, Regional Language and Literature Education Study Program, 2021.59 pages. This research was carried out because considering the activities of the traditional gusaran tradition that hindered its extinction, as well as the large number of young people who had not preserved the traditional gusaran tradition. This study aims to describe the implementation of the gusaran traditional tradition, as well as the semiotic analysis that exists in the gusaran traditional tradition in Cibingbin District, Kuningan Regency. The method used in this research is descriptive. Data collection techniques used in this research are interviews, observation, and documentation. The results of the research are 1) the implementation of the traditional gusaran tradition in Cibingbin District, Kuningan Regency, which is divided into 3 parts (a) preparation: preparing offerings, worshiping (b) Core activities: bathing children, making up children, praying, brushing teeth, feeding children, member jewelery (c) closing: preparing sawer, sawer, prayer. The semiotics in the gusaran tradition are: 1 icon, namely (miserly), 4 indices (the smell of offerings smoke, the aroma of coffee water, the taste of coffee water, praying), 13 symbols (coins, wenghal, huntingu, fried chicken, yellow rice, coffee). bitter, sweet coffee, egg, umbrella, rice, turmeric, thread, food container). .